1999
DOI: 10.1053/cp.1999.v66.103172001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endotoxin administration on the pharmacokinetics of chlorzoxazone in humans

Abstract: This study showed that the inflammatory response to lipopolysaccharide (20 endotoxin units/kg/day for 2 days) in humans does not consistently alter chlorzoxazone hepatic metabolism. However, the significant increase in renal clearance of the glucuronidated metabolite suggests that renal tubular secretion may be increased in humans with acute endotoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…In our study, LPS treatment produced a significant increase (5.42-fold, P < 0.05) in the serum level of this protein (Fig. 4B), in keeping with an earlier report on clinical studies (Poloyac, Tosheva, Gardner, Shedlofsky, & Blouin, 1999). Notably, the level of CRP in the LPS-treated animals decreased insignificantly (P > 0.05) upon co-treatment with RC.…”
Section: Resultssupporting
confidence: 92%
“…In our study, LPS treatment produced a significant increase (5.42-fold, P < 0.05) in the serum level of this protein (Fig. 4B), in keeping with an earlier report on clinical studies (Poloyac, Tosheva, Gardner, Shedlofsky, & Blouin, 1999). Notably, the level of CRP in the LPS-treated animals decreased insignificantly (P > 0.05) upon co-treatment with RC.…”
Section: Resultssupporting
confidence: 92%
“…It could also be expected that the formation of 6-OHCZX would decrease by ECLPS in humans. As expected, following the oral administration of 500-mg CZX to twelve healthy male volunteers after two daily administration of 20-units/kg/day ECLPS, the AUC of 6-OHCZX was significantly smaller (10.6% decrease) than that in control volunteers (Poloyac et al, 1999).…”
Section: Chlorzoxazone (Czx)supporting
confidence: 79%
“…Thus, in this review, an attempt to explain changes in the pharmacokinetics of drugs reported in the literature was made in terms of hepatic CYP isozyme changes or urinary excretion changes in ECLPS rats. Although the pharmacokinetic changes of drugs in ECLPS rats have been studied (Tables III and IV), the studies on humans are scarce except CZX (Poloyac et al, 1999). Thus, the extrapolation of the present animal data to humans is hard to have conclusion.…”
Section: Resultsmentioning
confidence: 87%
“…We recently demonstrated that IL-6 and endotoxin-mediated downregulation of transporters in the liver is mediated by NF-κB and STAT3, which are key inflammation-induced transcription factors [2,44]. While we cannot directly translate data from rodent models to humans, it has been shown that there are similarities in inflammation-induced production of cytokines, transcriptional factors, and gene expression changes in humans [45][46][47].…”
Section: Discussionmentioning
confidence: 99%